Rebuke for the Ijtihad of the Prophet (Study of Q.S Al-Nisa’ [4]: 34 as a Verse ‘Itāb) - Syukron Affani (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2021)
As a human being, the Prophet was involved humanly in various dynamics of life. TheProphet used ijtihad reasoning and subjective tendencies, which are of course relative, inresponding to life's problems. As a messenger of Allah, the actions and words of theProphet are decisions for Muslims except for revelation with other provisions from Allahsuch as with Q.S al-Nisa ' 4:34; one of the verses that presents a lot controversialdiscussion. The Prophet's decision to qiṣāṣ a husband who committed violence against hiswife, his passion is to provide justice and protection to women, but the decision wasoverturned by Q.S al-Nisa ' 4:34 which came down with other provisions as well asnuances of reprimand to the Prophet. The problem to be revealed in this paper is why Q.Sal-Nisa ' 4:34 intervened in the Prophet's decision in responding to domestic violence. Thisresearch is a qualitative library research. The method of description is descriptive-analytical,which explains the basic construction of the Prophet's ijtihad and the significance of Q.Sal-Nisa 4:34 to be analyzed using a historical-hermeneutical approach. The generalconclusion from this paper is that Q.S al-Nisa' [4]: 34 places the issue of household andgender relations in the perspective of a social order that has been widely applied. Thedecision of the Prophet's qiṣāṣ itself is not wrong but tark al-awlā (leaving a better thing)As a human being, the Prophet was involved humanly in various dynamics of life. The Prophet usedijtihad reasoning and subjective and of course relative tendencies, in responding to life's problems. As a messenger of Allah, the actions and words of the Prophet are decisions for Muslims except for revelationwith other provisions from Allah such as with Q.S al-Nisa ' 4:34; one of the verses presenting a lot controversial discussion. The Prophet's decision to qiṣāṣ a husband who committed violence against his wife is intended to provide justice and protection to women, but the decision was overturned by Q.S al-Nisa ' 4:34 which came down with other provisions as well as nuances of reprimand to the Prophet. Theproblem to be revealed in this paper is why Q.S al-Nisa ' 4:34 intervened with the Prophet's decision inresponding to domestic violence. This research is a qualitative library research. The method of description isdescriptive-analytical, explaining the basic construction of the Prophet's ijtihad and the significance of Q.S al-Nisa 4:34 to be analyzed using a historical-hermeneutical approach. The general conclusion drawn from this paper is that Q.S al-Nisa' [4]: 34 places the issue of household-to-gender relations in the perspective of a social order that has been widely applied. The decision of the Prophet's qiṣāṣ itself is notwrong but tark al-awlā (leaving a better thing) because it can actually increase the escalation of domesticconflicts in patriarchal society. This research contributes to the academic discourse by offering a new perspective on the relationship between the Prophet's ijtihad and Qur'anic provisions, particularly in addressing gender and social dynamics.because it can actually increase the escalation of domestic conflicts in patriarchal society.